CDK1 serves as a potential prognostic biomarker and target for lung cancer. Issue 2 (February 2020) - Li, Mingyao; He, Fenyi; Zhang, Zhanchun; Xiang, Zhenfei; Hu, Danfei
Objective: Evidence from cell and mouse models and human tissues suggests that cyclin dependent kinase 1 (CDK1) is involved in lung cancer (LC) tumorigenesis. However, the different types of expression patterns and prognostic results of CDK1 need further analysis. Methods: In the current study, we assessed CDK1 expression and LC patient outcomes using data from the Oncomine, GEPIA, and Kaplan–Meier Plotter databases. Additionally, mutations in the CDK1 gene were analyzed by using the cBioPortal database. The expression of CDK1 was verified by real-time quantitative PCR using the Human Protein Atlas database and human tissues. Results: Expression of CDK1 was higher in lung adenocarcinoma and squamous cell lung carcinoma tissues than in normal lung samples. Moreover, CDK1 expression was linked to disease progression. Survival analysis indicated that upregulation of CDK1 was related to poor overall survival, low first progression, and post-progression survival in patients with LC. Conclusions: Our results indicate that CDK1 is a potential clinical target and prognostic biomarker for patients with LC.